Does Organizational Politics in Public Sector Mediates the Impact of Recruitment and Selection on Employee Performance? - Munaza Bibi; Rafique Ahmed Khan; Amir Manzoor (Market Forces, 2021)
The presence of nepotism and favoritism during recruitment and selection has become a major concern for developed and developing countries. Based on the social exchange theory, a framework was developed to evaluate contextual performance, adaptive performance, and task performance due to recruitment and selection practices in an organization. The study also investigated nepotism and favoritism as mediating variables between recruitment and selection, contextual performance, adaptive performance, and task performance. Moreover, data from 384 respondents working in tertiary care hospitals in Pakistan was collected and analyzed using confirmatory factor analysis and structural equation modeling. The study found that recruitment and selection substantially impact contextual performance, adaptive performance, and task performance. The study also found that nepotism and favoritism have a mediating effect on job performance. Furthermore, the current study is of significance for hospital managers to formulate strategies to overcome this phenomenon, particularly in the recruitment and selection process, which affects the healthcare employee’s performance.